The Influence of Emotional Intelligence and Interpersonal Communication on Employees’ Work Satisfaction at Education and Culture Office in West Kalimantan - Erna Oktafiani; M. Chiar; Sukmawati Sukmawati (STKIP Singkawang, 2019)
The process of reorganization of the application of Law Number 23 of 2014 concerning Regional Government, the moratorium of civil servants and the limited quota of participants on attending education and training leads to two factors of job satisfaction, namely organization, and management. This study aims to (1) determine the influence of leadership emotional intelligence with job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province; (2) To determine the effect of interpersonal communication with job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province; (3) To determine the influence of leadership emotional intelligence and interpersonal communication on job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province. The results obtained from this study are the emotional intelligence of leaders significantly influence the job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province, which means that the better the emotional intelligence of their leaders, the higher the job satisfaction of employees of the West Kalimantan Provincial Education and Culture Office. Second, interpersonal communication has a significant effect on the job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province, which means that the better interpersonal communication that exists between employees of the Department of Education and Culture of West Kalimantan Province, the higher the job satisfaction of employees. Third, leadership emotional intelligence and interpersonal communication together have a significant effect on job satisfaction of employees of the Department of Education and Culture of West Kalimantan Province. It means that the better the emotional intelligence of leaders and interpersonal communication that exists between employees of the Department of Education and Culture of West Kalimantan Province, the higher the job satisfaction of the employees.